Investimento privado: uma análise a partir das expectativas empresariais - Coelho, Yuri Pimentel (2021)
This paper discusses the behavior of private investment in Brazilian federative entities in the period between 2012 and 2018. More specifically, it seeks to understand, through an econometric analysis, which macroeconomic variables influence private investment decisions. Initially, the main theories about investment are reviewed. The candidate variables for the econometric study carried out below are extracted from this review, considering, in particular, the specificities of regional economies. The conclusions highlight the role played by the variables studied here on private investment.